(untitled) (Research, Society and Development, 2021)
Objective: Was to assess the health literacy of the population in the city of Jundiai in relation to the adoption of practical measures to prevent the disease COVID-19. Methodology: Cross-sectional study with 290 adults of epidemiological survey about COVID-19, being 150 with negative tests and 140 with positive tests. Through phone calls, it was applied the Health Literacy Scale (HLS-14), between October 2020 and April 2021. The Chi-Square test (p<0,05) was performed. Results: The majority of the sample was between 18 to 39 years old (46,6%, n=135), women 63,1% (n=183), with higher education 43,4% (n=126) and income of 3 or more minimum waged 49,3% (n=143). As for the routine, 62,1% (n=180) didn’t go out or just did it when necessary, 83,4% (n=242) followed with their families preventive measures and 68,3% (n=198) followed social distancing orientation. Low Health literacy was found in 48,6% (n=141) and it was associated with older age (p=0,004) and also with not understanding social distance as a preventive measure for COVID-19 (p=0,047). Conclusion: The results showed a connection between low health literacy and lack of awareness about social distance being a preventive measure, demonstrating how important is to invest in public policies of health literacy in order to control the pandemic.